2021
DOI: 10.1214/21-ejp640
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of weighted recursive and affine preferential attachment trees

Abstract: We study two models of growing recursive trees. For both models, the tree initially contains a single vertex u1 and at each time n ≥ 2 a new vertex un is added to the tree and its parent is chosen randomly according to some rule. In the weighted recursive tree, we choose the parent u k of un among {u1, u2, . . . , un−1} with probability proportional to w k , where (wn) n≥1 is some deterministic sequence that we fix beforehand.In the affine preferential attachment tree with fitnesses, the probability of choosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Interestingly, as observed in [5] and confirmed rigorously in [8,12,14], there is a critical condition on the weight distribution under which this model undergoes a phase transition, resulting in a Bose-Einstein condensation: in the limit, a positive fraction of vertices accumulate around vertices of maximum weight. In a similar model known as preferential attachment with additive fitness, introduced in [16] and studied mathematically in [3,23,34], vertices connect to previous vertices with probability proportional to the sum of their degree (or degree minus one) and their weight. A number of other interesting preferential attachment models with fitness have been studied, including a model of preferential attachment with both additive and multiplicative weights [16], a related continuous-time model which incorporates ageing of vertices [18], and discrete-time models with co-existing additive and multiplicative attachment rules [1,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, as observed in [5] and confirmed rigorously in [8,12,14], there is a critical condition on the weight distribution under which this model undergoes a phase transition, resulting in a Bose-Einstein condensation: in the limit, a positive fraction of vertices accumulate around vertices of maximum weight. In a similar model known as preferential attachment with additive fitness, introduced in [16] and studied mathematically in [3,23,34], vertices connect to previous vertices with probability proportional to the sum of their degree (or degree minus one) and their weight. A number of other interesting preferential attachment models with fitness have been studied, including a model of preferential attachment with both additive and multiplicative weights [16], a related continuous-time model which incorporates ageing of vertices [18], and discrete-time models with co-existing additive and multiplicative attachment rules [1,22].…”
Section: Introductionmentioning
confidence: 99%
“…It was also introduced independently by Janson in the case that all weights are one except at the root, motivated by applications to infinite-colour Pólya urns [21]. In [34], Sénizergues showed that a preferential attachment tree with additive fitness with deterministic weights is equal in distribution to an associated weighted random recursive tree with random weights, an interesting link between the two classes of models.…”
Section: Introductionmentioning
confidence: 99%
“…• in Peköz, Röllin, and Ross [71], as distributions of processes on walks, trees, urns, and preferential attachments in graphs, where these authors also consider what they call a Pólya urn with immigration, which is a special case of a periodic Pólya urn (other models or random graphs have these distributions as limit laws [20,85]);…”
mentioning
confidence: 99%
“…random variables, under an 8-th moment condition. Sénizergues [15] proved results about its degree distribution and height for a deterministic sequence of weights under very general assumptions (with more refined results about the height -maximum distance of a node to the root-in Pain and Sénizergues [13]). Finally, Iyer [9] and Lodewijks and Ortgiese [11] prove asymptotic results on, respectively the degree distribution and the largest degree of the wrrt with i.i.d.…”
Section: (A2)mentioning
confidence: 92%
“…This result is independent from Theorem 1.5; we state it because it has the potential for independent interest since wrrts are studied in unrelated contexts (see, e.g. [3,15], which we discuss in more detail later).…”
Section: Introductionmentioning
confidence: 97%